COVID-19 management in Iran and international sanctions - Hosien Pormasoumi; Daryoush Rostami; Khosro Jamebozorgi; Hosein Mirshekarpour; Jalal Heshmatnia (PAGEPress Publications, 2022)
Iran has one of the highest death rates from COVID-19 among Middle Eastern countries. In addition to having a better disease registration system compared to neighboring countries, many factors including economic conditions, have played an important role in increasing the number of mortality rate. This is while that during the Corona pandemic, Iran has been undergo severe sanctions by the United States, that has faced this country with a severe economic crisis. Considering the role of sanction on the country's health management in our study, we examined Iran's management plans against the Corona pandemic and the effect of sanctions on it. Quarantine and corona restrictions, on the one hand, and international sanctions, on the other hand, have put double pressure on the Iranian government. Although drugs and basic medical equipment are exempted from economic sanctions, direct and indirect effects of the sanctions have limited Iran's banking system and created widespread restrictions in the fields of trade, production, and investment. Fortunately, despite the sanctions, many hospitals had an appropriate performance in line with the health promotion program. It is obvious that economic sanctions have severe and harmful effects on public health and have led to poor health consequences in Iran, but attention to planning, standards and improving the quality of the hospital is an important issue in Corona management. Despite multiple mutations, this virus is likely to face with a more dangerous virus in the world future. Now, it is time to take appropriate management measures to remove these sanctions by relying on international solutions and interactions.